The Victim: A Romance of the Real Jefferson Davis - Dixon, Thomas, Jr., 1864-1946; Marchand, J. N. (Salt Lake City, UT : Project Gutenberg, 2006)
"The Victim: A Romance of the Real Jefferson Davis" by Thomas Dixon is a historical romance written in the early 20th century. The narrative delves into the life of Jefferson Davis, providing a dramatic portrayal of his characterization and events surrounding the Civil War, focusing on themes of sacrifice, valour, and destiny. The opening features pivotal historical figures and sets the stage for a blend of personal and political narratives. At the start of the novel, we are introduced to young Jefferson Davis and his interactions with family members, primarily his older brother and sister, as they prepare him for a journey to receive an education. The emotional undertones of family bonds and the boy's reluctant departure highlight the tension between duty and personal desire. Meanwhile, the prologue hints at the significant historical backdrop against which these intimate stories unfold, foreshadowing the hardships and turbulent times that lie ahead for Jefferson and the South during the Civil War. (This is an automatically generated summary.)
Release date is 2006-06-30
E-text prepared by David Garcia, Paul Ereaut, and the project Gutenberg Online Distributed Proofreading Team
Keywords: United States -- History -- Civil War, 1861-1865 -- Fiction; Historical fiction, American; Davis, Jefferson, 1808-1889 -- Fiction